Economic analyses of behavioral health intervention implementation: Perspective on stakeholder engagement - Raciborski, Rebecca A.; Woodward, Eva N.; Painter, Jacob T. (Frontiers in Psychiatry, 2022)
To provide full potential benefits to patients, behavioral health interventions often require comprehensive and systematic implementation efforts. The costs of these efforts should therefore be included when organizations decide to fund or adopt a new intervention. However, existing guidelines for conducting economic analyses like cost-effectiveness analyses and budget impact analyses are not well-suited to the complexity of the behavioral healthcare pathway and its many stakeholders. Stakeholder engagement, when used effectively with recent innovations in economic analysis, advance more equitable access to interventions for individuals living with behavioral health conditions. But early and ongoing stakeholder engagement has not yet been incorporated into best-practice guidelines for economic evaluation. We discuss our perspective, as researchers and clinicians in a large integrated health system, on how the integration of stakeholder engagement with existing economic analysis methods could improve decision-making about implementation of behavioral health interventions.